Object Placement for High Bandwidth Memory Augmented with High Capacity Memory - Laghari, Mohammad; Unat, Didem (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2017: Anais do XXIX International Symposium on Computer Architecture and High Performance Computing, 2017)
High bandwidth memory (HBM) is a new emerging technology that aims to improve the performance of bandwidth limited applications. Even though it provides high bandwidth, it must be augmented with DRAM to meet the memory capacity requirement of any applications. Due to this limitation, objects in an application should be optimally placed on the heterogeneous memory subsystems. In this study, we propose an object placement algorithm that places program objects to fast or slow memories in case the capacity of fast memory is insufficient to hold all the objects to increase the overall application performance. Our algorithm uses the reference counts and type of references (read or write) to make an initial placement of data. In addition, we perform various memory bandwidth benchmarks to be used in our placement algorithm on Intel Knights Landing (KNL) architecture. Not surprisingly high bandwidth memory sustains higher read bandwidth than write bandwidth, however, placing write-intensive data on HBM results in better overall performance because write-intensive data is punished by the DRAM speed more severely compared to read intensive data. Moreover, our benchmarks demonstrate that if a basic block makes references to both types of memories, it performs worse than if it makes references to only one type of memory in some cases. We test our proposed placement algorithm with 6 applications under various system configurations. By allocating objects according to our placement scheme, we are able to achieve a speedup of up to 2x.